Numerical VIV analysis of a single elastically-mounted cylinder: Comparison between 2D and 3D URANS simulations. (July 2021) - Martini, Simone; Morgut, Mitja; Pigazzini, Riccardo
Abstract: In this paper the numerical simulations of the flow around an elastically-mounted circular cylinder with one degree of freedom (1-DOF) with small damping parameter and small mass ratio are presented. The simulations are performed for subcritical Reynolds numbers ( 2 . 0 ⋅ 1 0 3 < Re < 1 . 3 < 1 0 4 ), using the URANS (Unsteady Reynolds Averaged Navier Stokes) approach in combination with the SST (Shear Stress Transport) turbulence model. The simulations are carried out on 3D as well as 2D meshes. From the overall results it seems that the bi-dimensional approach could be effectively applied in the lower branch, while major discrepancies are present in the upper branch. The detailed analysis of the wake flow characteristics shows that the three dimensionality of the flow is stronger in the transition zones between the different branches. The extensive comparison between the computational simulations and the experimental results presented in this paper could be considered the "start point" in order to select the proper grid model depending on the requested accuracy.